Estimating intra-seasonal photosynthetic discrimination and water use efficiency using δ13C of leaf sucrose in Scots pine. (18th October 2022) - Tang, Yu; Schiestl-Aalto, Paulina; Lehmann, Marco M; Saurer, Matthias; Sahlstedt, Elina; Kolari, Pasi; Leppä, Kersti; Bäck, Jaana; Rinne-Garmston, Katja T
Abstract: Sucrose has a unique role in recording environmental and physiological signals during photosynthesis in its carbon isotope composition (δ 13 C) and transport of the signal to tree rings. Yet, instead of sucrose, total organic matter (TOM) or water-soluble carbohydrates (WSC) are typically analysed in studies that follow δ 13 C signals within trees. To study how the choice of organic material may bias the interpretation of δ 13 C records, we used mature field-grown Scots pine ( Pinus sylvestris ) to compare for the first time δ 13 C of different leaf carbon pools with δ 13 C of assimilates estimated by a chamber-Picarro system (δ 13 CA_Picarro ), and a photosynthetic discrimination model (δ 13 CA_model ). Compared with sucrose, the other tested carbon pools, such as TOM and WSC, poorly recorded the seasonal trends or absolute values of δ 13 CA_Picarro and δ 13 CA_model . Consequently, in comparison with the other carbon pools, sucrose δ 13 C was superior for reconstructing changes in intrinsic water use efficiency (iWUE), agreeing in both absolute values and intra-seasonal variations with iWUE estimated from gas exchange. Thus, deriving iWUE and environmental signals from δ 13 C of bulk organic matter can lead to misinterpretation. Our findings underscore the advantage of using sucrose δ 13 C to understand plant physiological responses in depth. Abstract : Comparison of assimilate δ 13 C values estimated from different leaf carbon pools, Picarro measurements, and modelled data demonstrates the potential for misinterpretation arising from bulk organic matter δ 13 C analysis.